(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study investigates the effectiveness of context-based vocabulary instruction compared to traditional decontextualized methods in English as a Foreign Language (EFL) classrooms. A quasi-experimental design was employed with 60 intermediate-level university students divided into an experimental group (n=30) receiving vocabulary instruction through authentic reading contexts and a control group (n=30) taught via word-list memorization. Data were collected through pre-tests, immediate post- tests, delayed post-tests administered four weeks after the intervention, and productive vocabulary tests. Results revealed that context-based instruction produced statistically significant improvements across all dimensions. The experimental group outperformed the control group on post-tests (t(58) = 4.87, p < 0.001, d = 1.26), demonstrated 34% superior long-term retention, and exhibited markedly higher productive vocabulary use. The findings support the integration of contextual approaches into EFL vocabulary curricula.